PENGEMBANGAN BAHAN AJAR MENGGUNAKAN MODEL ADDIE PADA MATERI STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN SMA KURIKULUM 2013 - Nadia Alima Fadhila; Nur Widya Setyaningsih; Rizqi Rahma Gatta; Rio Christy Handziko (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
This study aims to describe the development of teaching materials, Structure, and Function of Plant Networks with the ADDIE Model and material validation as well as product design for teaching materials development using the ADDIE model. This is a research development. I Validation of the media booklet instrument was carried out by two validators, namely material experts (content feasibility aspects, presentation feasibility aspects, and language assessments) and media experts (size, cover design, content design, layout, content typography, as well as illustrations and pictures). The results obtained are the product of the development of teaching materials in the form of a booklet arranged based on the ADDIE model. While the results of the validity test get a total validation mean of 3 for the material in the booklet and 3.87 for the media design of the booklet. Comments from the validators, namely on the material aspect in the form of improving the presentation of the material to make it easier to read, while the media aspect added facts and examples of cells, tissues, and plant organs in the form of photos and illustrationsKata kunci: ADDIE, bahan ajar, jaringan tumbuhan, kurikulum 2013.